2012
DOI: 10.1007/s11434-012-5200-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrochemical properties of re-synthesized LiCoO2 from spent lithium-ion batteries

Abstract: A new idea for reuse of the cathode materials of lithium-ion batteries (LIBs) is investigated to develop an environmentally friendly process for recycling spent batteries. LiCoO 2 is re-synthesized from spent LIBs by leaching and a sol-gel method calcined at high temperature. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) are employed to study the reactions occurring calcination that are responsible for the weight losses. X-ray diffraction (XRD) and scanning electron microscopy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Direct recovery is a low-cost technique, which contributes to several money savings [246]. The re-synthesis of spent LiCoO2 with a process of leaching followed up by sol-gel method, with calcination at high temperatures, is found to produce excellent cycle life performance in regenerated batteries [190].…”
Section: Physical Methodsmentioning
confidence: 99%
“…Direct recovery is a low-cost technique, which contributes to several money savings [246]. The re-synthesis of spent LiCoO2 with a process of leaching followed up by sol-gel method, with calcination at high temperatures, is found to produce excellent cycle life performance in regenerated batteries [190].…”
Section: Physical Methodsmentioning
confidence: 99%
“…Li et al 131 reported a process consisting of acid leaching and sol−gel for recycling spent LIBs. Citric acid was first used as leaching agent to leach Co and Li, and then as a chelating agent for the sol−gel process.…”
Section: LImentioning
confidence: 99%
“…Pored interesa za dobijanjem pojedinačnih metala iz potrošenih litijum jonskih baterija [1,4,[10][11][12][13][14], u poslednje vreme postoji sve veća tendencija da se resintetiše katodni materijal iz potrošenih litijum jonskih baterija. Najčešće metode resinteze su sol-gel metoda [15][16][17][18], metoda koprecipitacije [19][20][21] i reakcija u čvrstom stanju [22][23][24]. Metodom koprecipitacije i sol gel metodom se dobijaju čestice nanometarskih dimenzija [15][16][17][18][19][20][21] dok se metodom reakcije u čvrstom stanju dobijaju čestice mikrometarskih dimenzija [22][23][24].…”
Section: Uvodunclassified
“…Najčešće metode resinteze su sol-gel metoda [15][16][17][18], metoda koprecipitacije [19][20][21] i reakcija u čvrstom stanju [22][23][24]. Metodom koprecipitacije i sol gel metodom se dobijaju čestice nanometarskih dimenzija [15][16][17][18][19][20][21] dok se metodom reakcije u čvrstom stanju dobijaju čestice mikrometarskih dimenzija [22][23][24]. Dobijanje nanometarskih čestica je od interesa zbog njihove velike specifične površine.…”
Section: Uvodunclassified